Perencanaan Bahan Baku Cat Leatherpaint Menggunakan Metode Material Requirement Planning - Horasman Purba; Andung Jati Nugroho (Politeknik Kampar, 2024)
PT. Yogyakarta Art Creations is an industry that produces paint, shoes, jeans, which are divided into two materials, foam and canvas. This company has two types of shoe paint which are produced, including types of paint made from canvas and paint made from leather with various colors. The raw materials needed in the manufacture of these paints include water, color pigments, paint reinforcers, paint fasteners and special mixtures for make canvas paint and leather. in each period of one month there can be up to 700 pcs of products with different types of products, with a total income of IDR 125,000,000 each month. However, from February 2023 to March 2023, the company experienced a swelling of raw materials that did not match the predetermined data, so it was necessary to plan shoe polish production in order to determine the appropriate supply of raw materials for each period. The Material Requirement Planning (MRP) method is used to determine what materials or components must be made or purchased, how much is needed and when it is needed. Based on research that has been carried out through several data processing, it can be concluded that raw material inventory control is carried out by forecasting based on past data requests (February 2022 to March 2023) and then the lotting technique used to assist the MRP calculation process is the Method Lot for lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ).